A case report of uterine inversion after home delivery - M, Sena-Martins; V, Tadini; B, Bolsonaro-Guilherme; C, Mariani-Neto; ABN, Pires; LL, Lucato; AN, Soares; JC, Xavier; BACB, Teixeira; SL, Faro; et al. (Clinical Journal of Obstetrics and Gynecology, 2021)
Puerperal acute uterine inversion is a rare obstetric condition observed as a serious complication during the third stage of labor. Reported as one of the causes of postpartum haemorrhage, it commonly requires quick diagnosis and surgical treatment in order to reduce morbidity and lethality. The authors describe a case of uterine inversion with hypovolemic shock after home birth, brought to Hospital Leonor Mendes de Barros. The purpose of this article is to describe a case of acute uterine inversion and its management and a review of aetiology, predictive and risk factors, diagnosis and treatment.